(untitled) (Journal of Nobel Medical College, 2015)
Background: There are more than 1 million patients with a permanent colostomy and the number is increasing by the rate of 100 000 per year. Clients with a new stoma must master multiple psychomotor skills to remove their pouch, clean the stoma and peristomal skin and empty and dispose of effluent from the pouch. Stoma care self-efficacy has been positively related to ostomy adjustment. Objective: To assess knowledge and practice of stoma care among ostomates. Method: This is a simple descriptive cross sectional study. A total of 94 ostomates who met eligible criteria were purposively sampled. Stoma self care efficacy scale and semi-structured questionnaire was used and face to face interview was done. Data were analyzed using SPSS version 16 program. T test was used to see the mean difference. Result: The knowledge of ostomates on normal stoma and complication of stoma was adequate (61.7%). Majority (92.6%) respondents had good daily care practice like emptying pouch, hand washing before and after procedure and cleaning stoma. Majority of the ostomates suffered from physical problem (89.4%). Of which maximum 72.3% had peristomal skin irritation, then came leakage and odour. More than half (64.9%) of ostomates had higher efficacy. Conclusion: On the basis of findings, it is concluded that there was significant difference in mean knowledge of ostomates with variables pre-operative teaching, training on stoma care, living with stoma for more than 12 months. There was significant difference in mean self care efficacy with variables duration of living with stoma and training on stoma care. Thus training on stoma care should be provided frequently to further improve self care efficacy. Journal of Nobel College of Medicine Vol.4(1) 2015: 36-45